Błagam :)

Uzupełnij.
a) .... - .../3(6a+9b) = -1 +2a+3b
b) 2(-3x² - 4) -5(-2x² +7) = ....x² + ....
c)-(-29a -3b) +5(-2a-3b) = ....a +....b
d)6(1/2p²-1/3q²+2/3) -2(1/2q²-p²-1)+3=....p²+....q²+....
e)4(2a-3b-2) -3(5a+2b-4) =5(5a+2b-7) = ....a-....b-....

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T17:50:58+01:00
Uzupełnij.
a) -1 - 1/3(6a+9b) = -1 +2a+3b
b) 2(-3x² - 4) -5(-2x² +7) = -6x² -8+10x²-35 = 4x² + ( -43)
c)-(-29a -3b) +5(-2a-3b) = 29a+3b-10a-15b = 19a +(-12b)
d)6(1/2p²-1/3q²+2/3) -2(1/2q²-p²-1)+3=
3p²-2q²+4-q²+2p²+2+3 = 5p²+(-3q²)+ 9
e)4(2a-3b-2) -3(5a+2b-4) +5(5a+2b-7) =
8a-12b-8-15a-6b+12+ 25a+10b-35=
18a-8b-31
1 5 1